UTILIZATION OF ORGANIC WASTE TO ORGANIC FERTILIZER IN THE ELEMENTARY SCHOOLS OF SIJUNJUNG DISTRICT - Faisal, Faisal; Diningrat, Diky Setya; Siregar, Batumahadi; Budiarta, Kustoro (Universitas Negeri Medan, 2019)
The Program for Applying Appropriate Technology (PPTTG) aims to utilize organic waste into organic fertilizer in SD Negeri 13 Muaro and SD Negeri 3 Muaro, Sijunjung District, Sijunjung Regency, West Sumatra Province. This program is carried out based on an analysis of problems faced by partners, including: (1) awareness of school residents disposing of rubbish where it is still low, (2) the amount of organic waste generated every day so that it becomes a serious problem for schools, (3) schools have not been able to treating organic waste into high quality products. Seeing this problem, it is necessary to look for solutions in the form of: (1) mentoring waste management literacy, (2) socialization of the utilization of organic waste into organic fertilizer, and (3) assistance using organic waste to technology-based organic fertilizer. The results of the application of technology showed that the average success rate of the program reached 85,11% with the Good category. This means that the application of technology in the form of utilizing organic waste into organic fertilizer can be implemented well in elementary schools in Sijunjung Regency.Keywords: Organic Waste; Organic Fertilizer; Elementary School.